EFFECT OF DIFFERENT DOSES OF ALOE VERA VERSUS INDOMETHACIN ON SODIUM AND WATER RETENTION IN HEALTHY RATS - Arain, Abdul Qudoos; Hussain, Mazhar; Chiragh, Sadia (Journal of Postgraduate Medical Institute, 2017)
Objective: To compare the dose dependent effect of chloroform extract of aloe vera gel on sodium and water retention in rats with indomethacin and control. Methodology: This randomized controlled trial was conducted at Post Graduate Medical Institute, Lahore in which thirty male Sprague Dawley rats were divided in to five groups. First group was control (CTL), second was given indomethacin 3 mg/kg (INDO) while groups AVL, AVM, and AVH were given 200, 400 and 800 mg/kg doses of Aloe vera gel extract orally for a period of 28 days. Body weight, blood haematocrit level, total sodium excretion and serum sodium and potassium concentrations were measured. SPSS version 17 was used for data analysis. Results: Comparison of treatment groups with control at end of study showed significant weight gain in group INDO and AVH (p value <0.001). INDO and AVH groups also showed a significant decrease in total sodium excretion (p value 0.001 and 0.015). The mean haematocrit decreased insignificantly in groups INDO and AVH, while serum sodium level increased insignificantly in group INDO. Highest serum potassium level was observed in group INDO (p value 0.001) and the lowest was found in group AVH but difference was not significant as compared to control. Conclusion: High dose of aloe vera gel extract causes significant sodium and water retention in healthy rats, which was still less than that of indomethacin.